Representation, aesthetics and performance. The iconic character of missing persons images - Zamora Sauma, Rocío (2016)
Against the continuous assertion of the incapability of represent events, I present the next question: Where does originate the idea about the unimaginable, irrepresentable, unspeakable character of the genocide processes of 20th century? To answer this question I expound, in the first part, the iconic character of the missing persons portraits, in order to understand the frame in which can be established the assertion about the irrepresentable.